Penetapan Kadar Flavonoid Total Ekstrak Etanol 70% Daun Bayam Brazil (Althernanthera sisso) Dengan Metode Spektrofotometri UV-Vis - Nur Humaira Marwati; Revita Saputri; Eka Fitri Susiani (BORNEO JOURNAL OF PHARMASCIENTECH, 2024)
Brazilian Spinach (Althernanthera sisso) leaves are known to have a high natural antioxidant activity content of 3.7 ppm. Antioxidants have an important role in the human body to prevent damage caused by free radicals. One of the compounds that have antioxidant activity is flavonoids. Based on this description, it is necessary to know the content of total flavonoids in A. sisso This study aims to determine qualitatively using Thin Layer Chromatography (TLC), while quantitatively using UV-Vis spectrophotometry. Maceration method with 70% ethanol solvent was used to extract Brazilian spinach leaves. Thin Layer Chromatography (TLC) followed by spray reagents was used to test the flavonoid compounds. Quercetin reagent was used to determine total flavonoid levels, while AlCl3 was used to determine total flavonoid levels. The results of this qualitative test showed the presence of flavonoids, and in the quantitative test using UV-Vis spectrophotometry the total levels of flavonoids were 70.890 ± 1.723% w/w quercetin equivalent. The 70% ethanol extract of A. sisso leaves contains flavonoids so that it has the potential to be developed as a medicinal plant